Intravenous irons: from basic science to clinical practice - Bhandari, S; Pereira, D; Chappell, H; Drakesmith, H (MDPI, 2018)
Iron is an essential trace mineral necessary for life, and iron deficiency anaemia (IDA) is one of the most common haematological problems worldwide, affecting a sixth of the global population. Principally linked to poverty, malnutrition and infection in developing countries, in Western countries the pathophysiology of IDA is primarily linked to blood loss, malabsorption and chronic disease. Oral iron replacement therapy is a simple, inexpensive treatment, but is limited by gastrointestinal side effects that are not inconsequential to some patients and are of minimal efficacy in others. Third generation intravenous (IV) iron therapies allow rapid and complete replacement dosing without the toxicity issues inherent with older iron preparations. Their characteristic, strongly-bound iron-carbohydrate complexes exist as colloidal suspensions of iron oxide nanoparticles with a polynuclear Fe(III)-oxyhydroxide/oxide core surrounded by a carbohydrate ligand. The physicochemical differences between the IV irons include mineral composition, crystalline structure, conformation, size and molecular weight, but the most important difference is the carbohydrate ligand, which influences complex stability, iron release and immunogenicity, and which is a unique feature of each drug. Recent studies have highlighted different adverse event profiles associated with third-generation IV irons that reflect their different structures. The increasing clinical evidence base has allayed safety concerns linked to older IV irons and widened their clinical use. This review considers the properties of the different IV irons, and how differences might impact current and future clinical practice.